Hypothetical lung structure of Brachiosaurus (Dinosauria: Sauropoda) based on functional constraints - S. F. Perry; C. Reuter (Fossil Record, 1999)
Comparison of avian and crocodylian lung structure suggests a basic archosaurian structural type, consisting of four rows of chambers that radiate independently from an intrapulmonary bronchus. The later structure is cartilage-reinforced cranially. Caudally, the cartilage reinforcement diminishes and the radiating pattern of tubular chambers becomes irregular. The presence of extensive pneumatic spaces in the dorsal vertebrae combined with the extremely large size of Brachiosaurus suggests that the dorsal margin of the lungs was strongly attached to the body wall, thus restricting lung inflation in this region. By analogy with similarly structured testudine lungs, it is highly probable that the ventral part of the very large and cavernous lungs consisted of sac-like chambers, which acted as air reservoirs and also ventilated the gas exchange tissue, which was concentrated dorsally. Die Strukturen der Vogel- und der Krokodillunge deuten auf einen basalen Bauplan der Archosaurierlunge hin, der aus vier Reihen von Kammern besteht, die von einem intrapulmonalen Bronchus entspringen. Dieser ist cranial knorpelig verstärkt. Caudal vermindert sich die knorpelige Verstärkung und das Verteilungsmuster der Kammern wird ungleichmäßig. Die Anwesenheit von pneumatischen Räumen in den Wirbelkörpern und die extreme Größe von Brachiosaurus deuten daraufhin, daß der dorsale Bereich der Lunge mit der Körperwand verbunden war. Dies schränkte die Belüftung der Lunge in dieser Region ein. In Analogie zu den ähnlich strukturierten Schildkrötenlungen ist es höchst wahrscheinlich, daß der ventrale Teil der sehr großen Lungen aus sackartigen Kammern bestand, die als Luftreservoir dienten und das dorsal liegende Gasaustauschgewebe ventilierten. doi:10.1002/mmng.1999.4860020104